Factor income shares and micro-level restructuring: An analysis of Finnish manufacturing - Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2002)
This paper examines the relationship between productivity-enhancing restructuring at the micro level and changes in aggregate factor income shares in Finnish manufacturing. As a framework we make use of a simple model where long-run aggregate productivity growth is determined by successive technology steps that are taken in the new plants by seizing new technological opportunities. This requires investments into tangible and intangible capital that involve sunk costs. Wages are determined through centralised bargaining. In the equilibrium wages are set so that the present value of profits of the plants are squeezed to zero. Identical workers share the same wage level and the wages are increased at the rate of previous aggregate productivity growth, so that in the steady state factor income shares are unchanged. According to the model, the larger the new technological opportunities, the higher is the R&D intensity and the higher is the restructuring component of aggregate productivity growth and the larger is the income share of capital. We find evidence that the decline in the aggregate labour share can be very much explained by the transfer of payroll shares from high labour income share (poorly profit-making) plants to low labour income share (profitable) plants. Empirical findings about the micro-level sources of aggregate productivity growth and the micro-level features of the changes in aggregate income shares are consistent with the interpretation that Finnish manufacturing experienced a positive technology shock in the latter part of the 80s. Some signs of the chilling of restructuring can be found in the late 90s. – – Tutkimuksessa selvitetään tuottavuutta vahvistavan mikrotason rakennemuutoksen ja aggregaattitason tulo-osuusmuutosten välistä yhteyttä Suomen tehdasteollisuudessa. Tarkastelun kehikkona on yksinkertainen malli, jossa pitkän aikavälin aggregaattitason tuottavuuskasvu määräytyy peräkkäisissä teknologia-askeleissa, jotka tehdään uusissa toimipaikoissa tarttumalla uusiin teknologisiin mahdollisuuksiin. Tämä vaatii investointeja aineelliseen sekä aineettomaan pääomaan, josta aiheutuu upotettuja kustannuksia. Palkoista sovitaan keskitetysti. Tasapainossa palkat ovat asettuneet siten, että toimipaikkojen voittojen nykyarvo on nolla. Identtisillä työntekijöille on samat palkat ja palkkoja nostetaan samalla vauhdilla kuin aggregaattituottavuus on parantunut aikaisemmin, jolloin normaalioloissa tulo-osuudet pysyvät muuttumattomana. Mallin mukaan mitä enemmän on uusia teknologisia mahdollisuuksia, sitä korkeampi on T&K intensiteetti, sitä korkeampi on aggregaattitason tuottavuuskasvun rakennekomponentti ja sitä suurempi on pääoman tulo-osuus. Tutkimuksessa saadaan näyttöä siitä, että työn tulo-osuuden pieneneminen aggregaattitasolla voidaan paljolti selittää palkkaosuuksien siirtymällä korkean työn tuloosuuden (huonosti kannattavista) toimipaikoista matalan työosuuden (hyvin kannattaviin) toimipaikkoihin. Empiiriset havainnot aggregaattitason tuottavuuskasvun mikrotason lähteistä sekä aggregaattitason tulo-osuusmuutosten mikrotason piirteistä puhuvat sen puolesta, että Suomen teollisuus koki positiivisen teknologiashokin 1980-luvun jälkimmäisellä puoliskolla. Joitakin merkkejä saadaan siitä, että rakennemuutos on rauhoittunut 1990-luvun lopulla.
Keywords: J3; O12; 330; Labour income share; productivity; micro-level restructuring; technology shock; Produktivität; Reorganisation; Verarbeitendes Gewerbe; Finnland